Architectural models : construction techniques - Knoll, Wolfgang, ....-; Hechinger, Martin, ....- (Fort Lauderdale : Ross, 2007)
Make your next presentation a winner--it's easy with this four step guide! Your presentations become more persuasive when you rely on this uniquely thorough guide to building highly professional models. Knoll's Architectural Models covers every step of this make-or-break process. FIRST you'll gain insight into the many types of models, including building, site, landscape, garden, and special models. SECOND, coverage of materials and tools then helps you determine which media are best suited to convey your specific idea. THIRD, you discover effective new ways of setting yp your work area and preparing the work, with the aid of an extended checklist. FOURTH, you're taken step by step through the fabrication of the components--from base plates through building up sites to soldered structures. And, along the way, hundreds of photos and drawing highlight techniques and offer innovative model ideas.
Keywords: Modelbouw ; architectuur